The Relationship between Health Literacy and Physical Activity Level of Elderly Women in the City of Urmia - Fariborz fathi; Morteza Rezaei sofi (Mashhad University of Medical Sciences, 2017)
Background and objective: Health Literacy refers to cognitive and social skills which determine the motivation and knowledge intended for people to obtain information and access to understand and using them to promote and keeping fitness. Regular physical activity is necessary for human. The purpose of this study was to investigate the relationship between Health Literacy and physical activity level of elderly women in the of Urmia city. Methods: In this descriptive - correlation study of 120 elderly women of Urmia were selected. In Order to collect data, two questionnaire Functional Health Literacy of TOFHLA adults   and a physical activity questionnaire of Baekce was used. It was used SPSS software and one-sample T- test, and it was also conducted Pearson correlation and stepwise regression. Results: of 30% of the elderly had adequate Health Literacy 38/34 had inadequate health literacy and 31/64 had cross-border Health Literacy. Correlations were positive and significant correlation between adequate Health Literacy and physical activity were cross-border health physical activity in respectively. One-sample T-Tak results showed that the level Health Literacy in both access and reading in elderly women is higher than the average level in Urmia. Stepwise regression analysis showed that adequate health and cross-border Health Literacy can account for more than 80 percent of their sporting activities. Conclusion:  In order to promote physical activity levels of elderly women it should be improved their health literacy. By planning and designing useful training in the field of Health Literacy programs tailored to the elderly it can be done effective step to develop literacy skills in community health and physical health of elderly. Paper Type: Research Article